Loneliness and emotional self-disclosure of freshmen dormitory residents of UPV, Miagao. - Farillon, Premel Jean (2001.)
The present study was conducted to determine if a relationship exists between the level of loneliness and emotional self-disclosure tendency of freshmen dormitory residents. This study was also undertaken to determine if a significant difference exists in the level of loneliness between the male and female freshmen dormitory residents and between those respondents with home residence outside or within the province of Iloilo. This study wanted also to find out if a significant difference exists in the emotional self-disclosure tendency between the male and female freshmen dormitory residents and between those respondents with home residence outside or within the province of Iloilo. Fifty-six (56) freshmen dormitory residents staying in the two freshman residence halls of the University of the Philippines in the Visayas - Miag-ao dormitory served as respondents. Respondents were divided into two groups in terms of their residence and sex. Those respondents with home residence outside or within the province of Iloilo and those male and female respondents. Two standard tests were administered and total scores for each scale were computed. The results indicated that a significant difference (t=-2.240,p =.029) was found in the level of loneliness between the freshmen dormitory residents with home residence outside (X1 = 45.93) and within (X2 =40.33) the province of Iloilo. But no significant difference (t = .o96, p =.924) exists between the male and female respondents. The freshmen dormitory residents with home residence outside the province of Iloilo were found to be lonelier than those respondents within the province of Iloilo. A significant difference (t= - 2.724, p= .009) was also found in the emotional self-disclosure tendency between the male (X1 = 72.04) and female (X2 = 94.57) freshmen dormitory residents. But there is no significant difference (t=.954, p = .344) between the respondents with home residence outside (X1 = 79.28 and within (X2 =87.63) the province of Iloilo. Female respondents exhibited more extensive disclosure of personal information of their feelings of their depression, happiness, jealousy, anxiety, anger, calmness, apathy, and fear than the male respondents. Findings also showed tat there is calmness, apathy, and fear than the male respondents. Findings also showed that there is no significant relationship (r = .212, p = .116) between the level of loneliness and emotional self-disclosure tendency of freshmen dormitory residents.
Research Project (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Freshmen Dormitory Residents